Parkinson's disease : a guide to patient care - Tuite, Paul J. (Springer Pub. Co., 2009)
This book serves as a practical compendium on the management issues related to Parkinson's disease (PD). As a quick, user-friendly reference, the book covers all aspects of effectively managing PD, with discussions of symptoms, causes of PD, patient evaluation, and home care advice. Conveniently organized in bullet-point, encyclopedic format, Parkinson's Disease is the comprehensive, one-stop reference for health professionals treating patients with PD. Four key sections:.:.; Problems presents guidelines on addressing complications that occur during the disease process, including anxiety, hall.